2020
DOI: 10.1108/ribs-07-2020-0088
|View full text |Cite
|
Sign up to set email alerts
|

International market selection: an application of hybrid multi-criteria decision-making technique in the textile sector

Abstract: Purpose The selection of an international market (IMS) is a prime factor in the success and growth of a company. Therefore, the purpose of this study is to consolidate and apply a systematic methodology that contributes toward the evaluation of international markets and promotes entry into the export market of Antioquia’s textile companies. Design/methodology/approach Through a systematic literature review, the criteria and sub-criteria involved in the IMS process are identified and a total of 5 general crit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 95 publications
0
14
0
Order By: Relevance
“…This could be explained by the fact in the Nigeria's business environment and the economy's performance would be improved further by lowering costs rather than enhancing the quality. Moreover, the most important factor affecting textile‐clothing products is cost (Vanegas‐López et al, 2020), making quality and flexibility of secondary importance from economic perspective.…”
Section: Analysis Of Findingsmentioning
confidence: 99%
“…This could be explained by the fact in the Nigeria's business environment and the economy's performance would be improved further by lowering costs rather than enhancing the quality. Moreover, the most important factor affecting textile‐clothing products is cost (Vanegas‐López et al, 2020), making quality and flexibility of secondary importance from economic perspective.…”
Section: Analysis Of Findingsmentioning
confidence: 99%
“…In global trade, the textile and apparel manufacturing industry faces an intensively competitive market because of the lesser capital investment, minimum technological requirements and the lower barriers for the new entrants (Dickerson, 1999; Vanegas-López et al , 2020). In addition, apparel manufacturers have limited bargaining power over their customers because of the availability of alternative options (Keough and Lu, 2021).…”
Section: Background Of the Studymentioning
confidence: 99%
“…The extant literature on export studies provides evidence that imitates export strategy's significance on export success (Luis and David, 2004;Campos-García et al, 2020). Empirical studies propose that a firm's export performance is influenced by its strategies and the managerial capabilities to systematically execute those strategies (Luis and David, 2004;Liargovas and Skandalis, 2008;Teece et al, 1997;Vanegas-L opez et al, 2020;Aaby and Slater, 1989). Such strategies include product adaptation, export diversification, promotion and pricing strategy, competitive pricing and promotion transformation (Shamsuddoha and Ali, 2006).…”
Section: Effect Of Export Commitments On Supply Chain Agilitymentioning
confidence: 99%
“…By utilizing a hybrid MCDM method, Enjolras et al [27] highlighted the strong influence and association between innovation and export activities as critical elements affecting a firm's competitiveness. Vanegas-López et al [28] applied the AHP-TOPSIS method to identify the international target markets for Antioquia's textile companies. This research indicated that this was the first methodology used for international market selection in the exporting sector in Colombia and Latin America.…”
Section: Literature Reviewmentioning
confidence: 99%